Responsive ternary heterojunction material and preparation method and application thereof

CN117815390BActive Publication Date: 2026-10-20SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311680016.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2026-10-20
Estimated Expiration
2043-12-08

AI Technical Summary

Technical Problem

然而,氧化钛禁带宽度为3.0-3.2eV,限制了外场响应

Benefits of technology

[0017]第四方面,本发明提供了一种响应型三元异质结材料在制备光热杀菌和抗肿瘤材料中的应用,所述响应型三元异质结材料响应外场,在近红外光条件下实现光热杀菌和抗肿瘤。在近红外光刺激下,高导电性薄膜/金属氧化物基三元异质结可以光热转换,实现光热杀菌或抗肿瘤的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117815390B_ABST
    Figure CN117815390B_ABST
Patent Text Reader

Abstract

The application relates to a responsive ternary heterojunction material and a preparation method and application thereof. The responsive ternary heterojunction material comprises a metal base material, a metal oxide modified layer formed in situ on the surface of the metal base material, and a variable valence metal oxide layer and a high-conductivity thin film generated in situ on the surface of the metal oxide modified layer; wherein the metal oxide, the variable valence metal oxide and the high-conductivity material form a ternary heterojunction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for constructing a ternary heterostructure implanted on a metal surface and its application under external field (ultrasound, infrared, etc.) response. Specifically, it can be applied to acoustic dynamics synergistic acoustic-thermal sterilization and anti-tumor effects under ultrasound response, as well as photothermal sterilization and anti-tumor effects under infrared light response, belonging to the field of biomedical materials technology. Background Technology

[0002] Hard tissue repair and replacement materials play a crucial role in repairing hard tissue defects and reconstructing lost physiological functions in the human body. Major products include artificial joints, internal fixation systems, and dental implants.

[0003] Titanium and its alloys possess excellent biocompatibility and mechanical properties, making them commonly used as implant materials in artificial joints, dental implants, and internal fixation systems. However, existing titanium and alloys cannot meet additional application requirements such as antibacterial, osteogenic, and antitumor properties. Currently, implant surfaces with targeted functions are often designed by loading metals and their compounds, drugs, etc., with specific properties. For example, ion implantation technology is used to inject metallic silver and calcium into the titanium surface to obtain a titanium surface with both osteogenic and antibacterial properties (Patent authorization number CN103014646B: A method for modifying a titanium surface with both osteogenic and antibacterial properties). However, these designs struggle to simultaneously satisfy both antibacterial properties and long-term safety of the implant surface.

[0004] Currently, commonly used external field responses include ultrasound therapy, near-infrared photothermal therapy, and microwave ablation therapy to achieve therapeutic goals [Smart stimuli-responsive strategies for titanium implant functionalization in bone regeneration and therapeutics, Materials Horizons, 2023, Advance Article]. All external field responses require responsive materials. Reports indicate that biocompatible titanium oxide-based materials can achieve certain functions under external field response. However, the band gap of titanium oxide (3.0-3.2 eV) limits its external field response. Constructing titanium oxide-based heterostructures is a common method to reduce the band gap. Constructing titanium oxide-based heterostructures on the titanium surface can effectively achieve external field-responsive antibacterial and antitumor functions under external field stimulation [Journal of Hazardous Materials, 2022, 429128310][Small, 2023, 19, 2206265]. The main problem to be solved is how to construct highly responsive heterojunctions. This can be approached from the following two aspects: 1. Reduce the bandgap of the composite material; 2. Increase the transfer rate of excited electrons and reduce the electron-hole recombination rate. Summary of the Invention

[0005] Therefore, this invention provides a ternary heterojunction material implanted on a metal surface, its preparation method, and its application under external field response, thereby achieving acoustic-thermal synergistic acoustic-dynamic sterilization and anti-tumor properties under external field response, as well as photothermal sterilization and anti-tumor properties under near-infrared light response.

[0006] On one hand, this invention provides a responsive ternary heterojunction material, comprising: a metal substrate, a metal oxide modified layer formed in situ on the surface of the metal substrate, and a variable valence metal oxide layer and a highly conductive thin film formed in one step in situ on the surface of the metal oxide modified layer; wherein the metal oxide, the variable valence metal oxide, and the highly conductive material form a ternary heterojunction. The variable valence metal oxide is formed in situ on the surface of the metal oxide, and the two are mutually soluble without a clear interlayer interface. The thickness of the variable valence metal oxide layer can be controlled by process parameters, and the metal oxide and the variable valence metal oxide constitute a metal oxide-based heterojunction. Moreover, the variable valence metal oxide and the highly conductive thin film are prepared in situ in one step, and are generated simultaneously, exhibiting the characteristic of in-situ bonding.

[0007] In this invention, the composite of a bottom metal oxide and a middle variable-valence metal oxide can effectively reduce the bandgap of the composite material. The highly conductive thin film uniformly covering the surface of the middle variable-valence metal oxide can effectively improve the conduction rate of excited electrons. The metal oxide and the variable-valence metal oxide form a highly conductive thin film / metal oxide-based ternary heterojunction with the highly conductive thin film.

[0008] Preferably, the metal substrate is an implantable metal, including at least one of titanium and its alloys, tantalum and its alloys, and zirconium and its alloys.

[0009] Furthermore, preferably, the metal oxide modified layer is TiO2, Ta2O5, or ZrO2; The variable valence metal oxides are Ti2O3, Ti3O5, Ta2O3, TaO2, and ZrO. 2-x At least one of the following, wherein 0 < x < 2; the highly conductive film includes at least one of graphene nanosheets, molybdenum disulfide nanosheets, and MXene nanosheets; preferably, the thickness of the graphene nanosheets is < 10 nanometers, the thickness of the molybdenum disulfide nanosheets is < 10 nanometers, and the thickness of the MXene nanosheets is < 10 nanometers.

[0010] By adopting the above technical solution, a two-dimensional nanosheet structure is formed in situ on the surface of the metal oxide-based heterojunction, which has a larger specific surface area, abundant edges, and higher electronic conductivity. This helps to quickly extract electrons generated by the metal oxide-based heterojunction under external field response, thereby forming superoxide radicals or singlet oxygen. At the same time, it weakens electron-hole recombination, which is conducive to the formation of hydroxyl radicals from valence band holes. The synergistic effect of superoxide radicals or singlet oxygen and hydroxyl radicals achieves the purpose of antibacterial or antitumor.

[0011] Preferably, the thickness of the metal oxide modified layer is <20 micrometers; the thickness of the variable valence metal oxide layer is 10-5000 nm, the variable valence metal oxide and the metal oxide are mutually soluble, and there is no obvious interlayer interface; the thickness of the highly conductive film is <500 nm.

[0012] Furthermore, this invention provides a method for preparing a responsive ternary heterojunction material, comprising: (1) An oxidation technique is used to prepare a metal oxide modified layer on the surface of a metal substrate; (2) A metal substrate with a metal oxide modified layer on its surface is placed in a plasma-enhanced chemical vapor deposition device, and a precursor material is introduced to form a variable valence metal oxide and a highly conductive thin film in situ on the surface of the metal oxide modified layer.

[0013] Preferably, the oxidation technique is anodic oxidation and / or micro-arc oxidation; The oxidizing electrolyte used for the anodic oxidation and micro-arc oxidation includes at least one of sulfuric acid, oxalic acid, hydrofluoric acid, sodium glycerophosphate, sodium hydroxide, potassium hydroxide, sodium tetraborate, and sodium silicate. The parameters for the anodic oxidation include: electrolyte concentration of 2–50 g / L, voltage range of 10–100 V, and time of 5–120 min; the parameters for the micro-arc oxidation include: electrolyte concentration of 5–100 g / L, voltage range of 280–700 V, time of 5–60 min, duty cycle of 5%–40%, and electrolyte temperature of 10–60 °C.

[0014] Preferably, the precursor material includes: a gaseous precursor, a liquid precursor, or a solid precursor; The gaseous precursor includes at least one of argon, hydrogen, methane, and acetylene; The liquid precursor includes at least one of titanium tetrachloride and titanium tetradimethylaminotetrachloride. The solid precursor includes molybdenum powder and sulfur powder.

[0015] Furthermore, preferably, when a gaseous precursor is selected, the parameters of the plasma-enhanced chemical vapor deposition apparatus include: the ionization power of the plasma generator is 50–400 W; the background pressure range is 0.1–1 Pa; the gas pressure range is 20–1000 Pa; the total flow rate of the gaseous precursor is controlled at 20–500 sccm; the reaction temperature is 400–800 °C; and the reaction time is 10–120 min.

[0016] Thirdly, this invention provides an application of a responsive ternary heterojunction material in the preparation of acoustic-thermal sterilization and antitumor materials. The responsive ternary heterojunction material responds to an external field, achieving acoustic-dynamic synergistic acoustic-thermal sterilization and antitumor effects under ultrasonic conditions. Through the above technical solution, when a highly conductive thin film / metal oxide-based ternary heterojunction is stimulated by an external field, such as ultrasound, the metal oxide and variable-valence metal oxide composite form a narrow-bandgap composite heterojunction, which can effectively generate more electron-hole pairs. Simultaneously, the highly conductive thin film at the top has excellent electron conduction properties, allowing electrons to be transferred to the outer surface of the material, thereby generating active free radicals to achieve antibacterial and antitumor effects. Furthermore, the highly conductive thin film / metal oxide-based ternary heterojunction exhibits excellent acoustic-thermal conversion effects, and under ultrasonic conditions, it can achieve acoustic-dynamic and acoustic-thermal synergistic sterilization or antitumor effects.

[0017] Fourthly, this invention provides an application of a responsive ternary heterojunction material in the preparation of photothermal sterilization and antitumor materials. The responsive ternary heterojunction material responds to an external field, achieving photothermal sterilization and antitumor effects under near-infrared light conditions. Under near-infrared light stimulation, the highly conductive thin film / metal oxide-based ternary heterojunction can undergo photothermal conversion to achieve photothermal sterilization or antitumor effects.

[0018] The present invention has the following beneficial effects; This invention employs oxidation technology to coat the surface of implantable metal substrates (such as titanium and its alloys, zirconium, tantalum, etc.) with a certain thickness of oxide-modified layer with good adhesion, without inducing significant internal stress. Variable-valence metal oxides form a metal oxide-based binary heterostructure in situ on the metal oxide surface, effectively reducing the band gap and facilitating response to external stimuli. This one-step generation of a highly conductive thin film / variable-valence metal oxide heterostructure effectively improves electron conduction. This results in a highly conductive thin film / metal oxide-based ternary heterojunction with a narrow band gap and high electron conduction rate, which is beneficial for achieving anti-tumor or antibacterial effects under external stimuli. Attached Figure Description

[0019] Figure 1 This invention utilizes scanning electron microscopy to examine the surface morphology of experimental samples prepared using the method described in Example 1. Figure 2 This invention utilizes scanning electron microscopy to examine the surface morphology of experimental samples prepared using the method described in Comparative Example 2. Figure 3 This invention utilizes scanning electron microscopy to examine the surface morphology of experimental samples prepared using the method described in Comparative Example 3; Figure 4 This invention utilizes scanning electron microscopy to examine the surface morphology of the experimental sample prepared using the method described in Comparative Example 4. Figure 5 This invention utilizes scanning electron microscopy to examine the surface morphology of the experimental sample prepared using the method described in Comparative Example 5; Figure 6 These are the Raman characterization results of the experimental samples prepared using the methods of Comparative Example 2 and Comparative Example 3, respectively, according to the present invention; Figure 7 These are the Raman characterization results of the experimental samples prepared using the methods of Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1, respectively. Figure 8 The X-ray diffraction results of the experimental samples prepared by the methods of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1 are respectively. Figure 9 The present invention uses the method of Example 1 to prepare the experimental sample, and selects the transmission electron microscope and electron diffraction characterization results; Figure 10 These are optical photographs of the experimental samples prepared by the methods of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1, respectively. Figure 11The absorbance test results of the experimental samples prepared by the methods of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1 respectively under ultrasonic conditions for the degradation of Rhodamine B. Figure 12 The absorbance test results of the experimental samples prepared by the methods of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 1 respectively under ultrasonic conditions for degrading methylene blue. Figure 13 The absorbance test results of the experimental samples prepared by the methods of Comparative Example 1, Comparative Example 2, Example 2 and Example 1 respectively under ultrasonic conditions for the degradation of methylene blue; Figure 14 These are the acoustic current response diagrams of samples prepared by the methods of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1 under ultrasonic conditions. Figure 15 These are images showing the acoustic-thermal conversion results of samples prepared using the methods of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1 under ultrasonic conditions. Figure 16 The band gap results are obtained by measuring and calculating the samples prepared by the methods of Comparative Examples 2, 3, 4 and Example 1 respectively using ultraviolet-visible absorption spectroscopy. Figure 17 This is a schematic diagram of the band structure and electron transfer of the sample prepared using the method of Example 1 of the present invention; Figure 18 The images show the surface morphology of Staphylococcus aureus inoculated onto the surfaces of samples prepared using the methods of Comparative Examples 1, 3, 4 and 1, with and without ultrasonic treatment. Figure 19 This is a schematic diagram of the process of implanting samples prepared by the methods of Comparative Example 1 and Example 1 into the rat femur: Step 1: Cut open the skin and periosteum of the rat femur to expose the distal end of the femur; Step 2: Use Kirschner wires to make holes; Step 3: Use forceps to place the implantation rod (2mm in diameter and 6mm in length) into the implantation hole; Step 4: Use absorbable sutures to suture the inner periosteum and use non-absorbable sutures to suture the outer skin. Figure 20 These are the Micro-CT analysis results of the test samples prepared by the methods of Comparative Example 1 and Example 1, respectively, according to the present invention. Detailed Implementation

[0020] The present invention will be further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.

[0021] In this invention, the responsive ternary heterojunction is a high-conductivity thin film / metal oxide / variable-valence metal oxide ternary heterojunction, whose structure includes: a metal substrate, a bottom metal oxide, a middle variable-valence metal oxide, and a top high-conductivity thin film. The variable-valence metal oxide is formed in situ on the surface of the metal oxide, and the two are mutually soluble without a clear interlayer interface. The thickness of the variable-valence metal oxide layer can be controlled by process parameters. The metal oxide and the variable-valence metal oxide constitute a metal oxide-based heterojunction. The variable-valence metal oxide and the high-conductivity thin film are prepared in situ in a one-step process, forming simultaneously and exhibiting in-situ bonding. The high-conductivity thin film / variable-valence metal oxide / metal oxide ternary heterojunction has a narrow bandgap and fast electron conduction, and can respond to stimuli such as external ultrasound and infrared light to achieve anti-tumor and bactericidal effects.

[0022] Taking graphene as an example of a highly conductive thin film and titanium or titanium alloy as an example of an implantable metal, a titanium oxide modified layer is formed on the surface of a titanium or titanium alloy substrate using an oxidation technique. This modified layer encapsulates the surface of the titanium or titanium alloy substrate. A central titanium trioxide modified layer is formed in situ on the surface of the bottom titanium dioxide modified layer. The titanium oxide and titanium trioxide form a binary narrow-bandgap titanium oxide-based heterojunction, and a graphene thin film is formed in situ on the titanium trioxide surface. The following exemplarily illustrates the preparation method of a highly conductive thin film / metal oxide-based ternary heterojunction material.

[0023] The graphene / titanium oxide-based ternary heterojunction is prepared by the following three steps: using a titanium or titanium alloy substrate as a sample, oxidizing the surface of the titanium or titanium alloy substrate using oxidation technology to obtain product Al. The above technical solution employs two oxidation techniques: anodic oxidation mainly utilizes the anodic reaction between the electrolyte in the electrolyte and the metal surface to form an oxide film; micro-arc oxidation mainly utilizes a high-voltage electric arc to form an oxide film on the metal surface. Both oxidation techniques can form a titanium dioxide modified layer on the substrate surface.

[0024] A further feature of this invention is that the oxidation technology employs one or both of anodic oxidation and micro-arc oxidation. By employing the above technical solution, the electrolyte is selected from any one or more of sulfuric acid, oxalic acid, hydrofluoric acid, sodium glycerophosphate, sodium hydroxide, potassium hydroxide, sodium tetraborate, and sodium silicate. By employing the above technical solution, a titanium dioxide modified layer is formed on the anode of the substrate titanium or titanium alloy, the thickness of which is between 20 nanometers and 20 micrometers, and the surface titanium dioxide modified layer has good adhesion. A further feature of this invention is that in S1, the oxidation time is controlled between 1 and 60 minutes; the oxidation voltage is set to 20-500V; and the electrolyte concentration is set to 2-50 g / L.

[0025] The product A1 obtained from the previous step is placed in a plasma-enhanced chemical vapor deposition (PECVD) apparatus. Through specific atmosphere heating and graphene preparation processes, highly active plasma groups are formed, leading to the in-situ formation of titanium trioxide (TiO2) on the surface of A1 in a single step, resulting in product A2. Simultaneously, graphene with a vertical nanosheet structure is formed on the surface of product A2, yielding product A3. Subsequent plasma-enhanced chemical vapor deposition aims to generate TiO2 in situ on the surface of titanium oxide. The formation of a binary narrow bandgap heterojunction between TiO2 and titanium dioxide further reduces the bandgap of the titanium oxide-based modified layer, making it more responsive to external stimuli. Simultaneously, the formation of a well-bonded graphene / TiO2 heterostructure on the TiO2 surface further facilitates electron conduction.

[0026] A further provision of the present invention is as follows: In S2, a reaction gas, including one or more of argon, hydrogen, methane, and acetylene, needs to be introduced into the vacuum tube of the plasma-enhanced chemical vapor deposition equipment. The pressure of the reaction gas is controlled between 20 Pa and 1000 Pa, and the total flow rate of the reaction gas is controlled within the range of 50-500 sccm. The temperature of the plasma chemical vapor deposition is set to 500-800℃, and the time of the plasma chemical vapor deposition is set to 30-120 min.

[0027] In this invention, oxidation technology and plasma-enhanced chemical vapor deposition (PECVD) are used in combination. This not only overcomes the difficulty of constructing graphene / titanium oxide-based ternary heterostructures using conventional methods, but also enables the one-step in-situ formation of titanium oxide and graphene on a titanium oxide base. This ternary heterostructure effectively reduces the band gap of the heterostructure and facilitates the conduction of excited electrons, resulting in an effective response to external fields (ultrasound, infrared light), thereby achieving bactericidal or antitumor effects under external field response. By adopting the above technical solution, titanium oxide and graphene are formed in one step, featuring in-situ generation characteristics, which is more conducive to the conduction of free electrons in graphene.

[0028] In this disclosure, a highly conductive thin film / metal oxide-based ternary heterojunction achieves acoustic-dynamic synergistic acoustic-thermal sterilization or anti-tumor activity under external field response, or achieves photothermal sterilization or anti-tumor activity.

[0029] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0030] Example 1 A method for preparing a responsive, highly conductive thin film / metal oxide-based ternary heterojunction, comprising the following two steps: S1: A titanium dioxide modified layer is prepared on the titanium surface using a micro-arc oxidation device. The electrolyte is a mixed solution of 38 g / L sodium tetraborate decahydrate and 14 g / L potassium hydroxide. A constant voltage mode of 400 V and a duty cycle of 20% are used. The electrolysis oxidation time is between 2 and 15 min. This process prepares the titanium dioxide modified layer on the titanium surface, yielding product A1. In other embodiments, the electrolyte can also be sodium silicate, sodium glycerophosphate, etc. In other embodiments, anodic oxidation can also be used to prepare the titanium dioxide modified layer on the titanium surface. S2: A1 is placed in an atmosphere... Inside the plasma chemical vapor deposition equipment, a plasma generator with a power of 100W was set, the heating rate was 5℃ / min, the reaction temperature was 750℃, and the reaction time was 1 hour. During the reaction, titanium trioxide was formed in situ on the surface of the titanium dioxide modified layer to obtain product A2, and graphene was formed on the surface of titanium trioxide to obtain product A3. The graphene has a vertical nanosheet structure, which further increases the specific surface area of ​​the material. The abundant graphene edges improve the electronic conductivity of the material. A3 is a graphene / titanium oxide-based ternary heterojunction composite material.

[0031] The first step in Example 1 involves micro-arc oxidation, which utilizes a high-voltage electric arc to form a titanium oxide modified layer on the sample surface. This modified layer exhibits excellent adhesion and produces specific surface structures (such as crater-like or grooved structures). By controlling these surface structures, acoustic metamaterials can be formed, exhibiting excellent acoustic-thermal conversion performance in ultrasonic response. The second step employs plasma-enhanced chemical vapor deposition (PECVD) to form titanium trioxide and vertical graphene in a one-step process. Specifically, during the first stage of sample heating to the target temperature (e.g., 750°C in Example 1), a reducing atmosphere is provided (a certain amount of hydrogen and argon are introduced; in Example 1, 80 sccm of argon and 5 sccm of hydrogen are introduced). When the temperature reaches 750°C, a carbon-containing precursor (2 sccm of methane in Example 1) is introduced, activating the plasma generator to produce carbon-containing plasma, hydrogen plasma, and argon plasma. The plasma has high activity, and at high temperatures, it forms titanium trioxide and vertical graphene in a one-step process with the bottom titanium dioxide, resulting in a graphene / titanium oxide-based ternary heterojunction material. By combining micro-arc oxidation technology with plasma-enhanced chemical vapor deposition, a robust titanium dioxide modified layer can be formed. By adjusting the bandgap of the surface material, a titanium dioxide and titanium trioxide heterostructure modified layer can be formed, effectively reducing the surface bandgap. The top-layer graphene effectively conducts free electrons and weakens the electron-hole recombination formed by external field excitation. This achieves the construction of a narrow bandgap heterostructure and an effective free electron conductor, which can respond efficiently to external fields and achieve the purpose of anti-tumor and antibacterial effects.

[0032] like Figure 1 As shown, the graphene / titanium oxide-based ternary heterostructure prepared by the preparation method in Example 1 was characterized. The surface morphology of the prepared sample was observed using a field emission scanning electron microscope (FESEM, Hitachi SU8200, Japan). As can be seen from the figure, after processing, the originally relatively flat titanium surface has a "groove-like" morphology, with a dense vertical nanostructure on the outer layer. The nanosheets are less than 10 nanometers thick and are uniformly wrapped on the surface of the grooves, which is beneficial for conducting the free electrons generated inside under the influence of the external field.

[0033] like Figure 7 As shown, a sample of the graphene / titanium oxide-based ternary heterostructure (BTO@VG(d) line in the figure) prepared by the method of Example 1 was prepared. Raman spectroscopy was used to test the characteristic peaks of graphene, and the sample was observed to have a peak at 1350 cm⁻¹. -1 1580cm -1 2700cm -1 The peaks at these locations are characteristic peaks, corresponding to the D peak, G peak, and 2D peak of graphene.

[0034] like Figure 8 As shown, the graphene / titanium oxide-based ternary heterostructure (BTO@VG lines in the figure) prepared by the method in Example 1 was experimentally prepared and characterized by XRD. The test range of 20° to 80° showed characteristic peaks corresponding to the (012), (104), (110), (113), (024), (116), and (214) crystal planes of titanium trioxide. The presence of characteristic peaks of rutile phase titanium dioxide confirms that this method can prepare titanium dioxide and titanium trioxide.

[0035] like Figure 9 As shown, the graphene / titanium oxide-based ternary heterostructure prepared by the method in Example 1 was experimentally prepared and characterized by transmission electron microscopy and selected area electron diffraction. Figure (a) shows the interface diagram, where the titanium oxide and titanium trioxide surfaces are perpendicular to the graphene layer, as shown in Figure (b). The thickness of the prepared perpendicular graphene film is approximately 378.5 nm. Figures (ce) show the lattice fringes of titanium trioxide, with the (012) interplanar spacing of 0.38 nm and the (116) interplanar spacing of 0.17 nm. Figures (g and i) show the selected area electron diffraction patterns, confirming the presence of both titanium trioxide and graphene. Figure (h) confirms the existence of a buffer layer of approximately 2.7 nm between the graphene and titanium oxide, which is formed due to the characteristics of plasma-enhanced chemical vapor deposition, as shown in Figure (j). Since this example uses a one-step in-situ method to construct titanium trioxide on the surface of titanium dioxide, titanium dioxide and titanium trioxide are miscible and have no obvious interface.

[0036] like Figure 10As shown, the graphene / titanium oxide-based ternary heterojunction prepared by the preparation method in Example 1 was experimentally prepared. The optical photographs of the samples show that titanium has a metallic luster, titanium dioxide is milky white, the graphene perpendicular to the titanium surface is black, titanium trioxide and titanium oxide are blackish-gray, and the graphene / titanium oxide-based ternary heterojunction is black.

[0037] like Figure 11 As shown, the graphene / titanium oxide-based ternary heterojunction prepared by the method in Example 1 was experimentally prepared. The degradation rate of Rhodamine B (RhB) on the sample was tested under ultrasonic conditions to evaluate the acoustic catalytic activity of the BTO@VG heterojunction sample (line (f) in the figure). Simply put, the sample was placed in a 24-well plate, 1 mL of Rhodamine B solution was added, and the sample was subjected to ultrasonic treatment (1.2 W cm⁻¹). -2 The sample was stimulated for 10 minutes at a 50% duty cycle and a 1MHz frequency. The absorbance at 550-750nm was read using a multi-mode microporous plate reader. The test results showed that Rhodamine B in the graphene / titanium oxide-based ternary heterojunction group had the lowest absorbance value, indicating that Example 1 had the best ultrasonic catalytic effect.

[0038] like Figure 12 As shown, the graphene / titanium oxide-based ternary heterojunction prepared by the method in Example 1 was experimentally prepared. The degradation rate of methylene blue (MB) on the sample was tested under ultrasonic conditions to evaluate the acoustic catalytic activity of the BTO@VG heterojunction sample. Simply put, the sample was placed in a 24-well plate, 1 mL of methylene blue solution was added, and the sample was subjected to ultrasonic treatment (1.2 W cm⁻¹). -2 Stimulated for 10 min with 50% duty cycle and 1 MHz frequency, the absorbance at 550-750 nm was read using a multi-mode microporous plate reader. The test results showed that Rhodamine B in the graphene / titanium oxide-based ternary heterojunction (BTO@VG, line (f) in the figure) group had the lowest absorbance value, indicating that Example 1 had the best ultrasonic catalytic effect.

[0039] like Figure 14 As shown, the graphene / titanium oxide-based ternary heterojunction prepared by the method in Example 1 was experimentally prepared, and its acoustic-current response under ultrasonic conditions was tested. The graphene / titanium oxide-based ternary heterojunction (BTO@VG, line (e) in the figure) exhibited the best acoustic-current response. Combined with... Figure 11 , Figure 12 and Figure 14 The results show that the experimental sample has the best ultrasonic response and the best ultrasonic catalytic effect.

[0040] like Figure 15As shown, the graphene / titanium oxide-based ternary heterojunction prepared by the method in Example 1 was used for experimental sample preparation. The acoustic-thermal conversion capability of the sample was tested under ultrasonic conditions. The temperature of BTO@VG reached 56.8℃ after ultrasonic treatment for 10 min. This indicates that the graphene / titanium oxide-based ternary heterojunction in this example has excellent acoustic-thermal conversion performance.

[0041] like Figure 16 As shown, the graphene / titanium oxide-based ternary heterojunction prepared by the method in Example 1 was used for experimental sample preparation. The ultraviolet-visible absorption spectrum of the sample was tested and the band gap of the sample was calculated. The band gap of the graphene / titanium oxide-based ternary heterojunction (BTO@VG, line (d) in the figure) was 1.62 eV, and the band gap of titanium dioxide (WTO in the figure) was 2.99 eV. Compared with titanium dioxide, it can be seen that the band gap of the graphene / titanium oxide-based ternary heterojunction is significantly reduced, which is more conducive to responding to external field stimulation.

[0042] like Figure 17 As shown, this diagram illustrates the band structure and electron transfer of the graphene / titanium oxide-based ternary heterojunction prepared by the method in Example 1 under external ultrasonic stimulation. Under ultrasonic excitation, electrons generated by titanium dioxide transfer to the valence band of titanium trioxide and recombine with holes in the titanium trioxide valence band. Free electrons generated by titanium trioxide rapidly transfer from the conduction band to graphene, where they combine with oxygen to form superoxide radicals. Furthermore, holes in the titanium dioxide valence band form hydroxyl radicals. These hydroxyl and superoxide radicals can induce superoxidative stress in tumor cells, triggering apoptosis and inhibiting tumor growth. Simultaneously, hydroxyl radicals and superoxide anions can also have a bactericidal effect.

[0043] like Figure 18 As shown, the graphene / titanium oxide-based ternary heterostructure prepared by the method in Example 1 was used for experimental sample preparation. The antibacterial effect of the BTO@VG sample under ultrasonic response was evaluated by in vitro culture of Staphylococcus aureus. 500 μL of 1.0 × 10⁻⁶ ppm was used. 7 Staphylococcus aureus was cultured at a concentration of [concentration] for 12 hours, then divided into two groups. One group received ultrasonic stimulation (1.0 W / cm²). -2 (50% duty cycle, 1 MHz, 10 min), one group received no ultrasonic stimulation. Bacteria were then fixed in glutaraldehyde solution for 24 h for dehydration. Finally, the bacterial morphology on the sample surface was observed using a scanning electron microscope (S-3400N, Hitachi Japan). Numerous round, spherical bacteria were observed on the surface of the untreated sample. However, a small number of damaged, irregularly shaped bacteria were observed on the surface of the ultrasonically treated sample. Based on the morphology of Staphylococcus aureus, it can be determined that the graphene / titanium oxide-based ternary heterostructure has a good external field-responsive bactericidal effect. Combined with... Figure 15 Test results and Figure 17As shown in the schematic diagram, under ultrasonic conditions, graphene / titanium oxide-based ternary heterojunctions can achieve synergistic acoustic-dynamic and acoustic-thermal sterilization. Based on the principle that graphene / titanium oxide-based ternary heterojunctions generate active free radicals and heat in response to an external field, we can prove that the graphene / titanium oxide-based ternary heterojunctions prepared in Example 1 can achieve anti-tumor effects under external field response.

[0044] Example 2 The difference between the preparation method in Example 2 and Example 1 is that the plasma chemical vapor deposition reaction time was adjusted to 30 minutes. The prepared sample was named TO@VG30.

[0045] like Figure 13 As shown, the sample prepared in Example 2 (TO@VG30, line (c) in the figure) exhibits excellent ultrasonic catalytic degradation of methylene blue under ultrasonic conditions. Compared to the sample prepared with a reaction time of 0 min (TO@VG0, line (b) in the figure), the sample prepared with a reaction time of 30 min demonstrates superior ultrasonic catalytic degradation of methylene blue. However, the sample prepared by the method in Example 1 (TO@VG60, line (d) in the figure) shows the best ultrasonic catalytic effect. This indirectly confirms that the prepared graphene / titanium oxide-based ternary heterostructure has excellent external field response and exhibits excellent ultrasonic catalytic (sonic dynamic) effect under ultrasonic stimulation.

[0046] Comparative Example 1 This comparative example directly uses commercially available pure titanium samples. For example... Figure 10 As shown in the optical photographs, titanium exhibits a metallic luster. Under ultrasonic response, the catalytic degradation efficiency of RhB and MB by the pure titanium sample is (…). Figure 11 (b) lines and Figure 12 (b) The lines are similar to those without a sample; the photocurrent of pure titanium under ultrasonic response is essentially zero. Figure 14 (a) lines)

[0047] like Figure 19 As shown, osteogenic evaluation was performed on the experimental samples obtained from Example 1 and Comparative Example 1 after in vivo ultrasound response antibacterial test. Eight-week-old male SD rats were selected, and experimental rods (2 mm in diameter, 8 mm in length) were implanted into the rat femurs. A certain amount of Staphylococcus aureus was added to the sample during implantation. The femoral fascia and external skin of the rats were sutured. The ultrasound-treated group (1.0 W cm) -2 (100% duty cycle, 1MHz, 10min), the group without ultrasound treatment was not subjected to ultrasound treatment and was euthanized after 6 weeks of feeding.

[0048] like Figure 20As shown, Micro-CT (micro computed tomography, SkyScan1176, Bruker, Belgium) was used to detect and evaluate the new bone formation in rat femoral samples. The Micro-CT scanning device was set to a voltage of 70kV, an X-ray current of 325μA, a 1.0mm aluminum filter, an image resolution of 18μm, a camera resolution of "Medica" (2000 pixel field width), and a scanning rotation step of 0.5°. The scanned images were reconstructed using NRecon (SKyScan) software. The reconstructed data were then analyzed for tissue morphology using DataViewe, CTAn, and CTVol software. The results showed that the bone surface area to bone volume (BS / BV) ratio of the ultrasound-treated graphene / titanium oxide-based ternary heterostructure sample was 25.2%. In contrast, the BS / BV of the untreated graphene / titanium oxide-based ternary heterostructure group was 8.3%, the ultrasound-treated titanium group was 10.0%, and the untreated titanium group was 9.5%. This indicates that the experimental sample in Example 1 responded better to ultrasound stimulation and exhibited better osteogenic activity after killing bacteria.

[0049] Comparative Example 2 The preparation method of Comparative Example 2 differs from that of Example 1 in that: the plasma-enhanced chemical vapor deposition step is reduced, a titanium sheet is used for micro-arc oxidation treatment to form a titanium dioxide modified layer, the electrolyte is a mixed solution of 38 g / L sodium tetraborate decahydrate and 14 g / L potassium hydroxide, a constant voltage mode of 400 V and a duty cycle of 20% is used, and the electrolytic oxidation time is between 2 min and 15 min to prepare a titanium dioxide modified layer on the surface of pure titanium, thus obtaining product A1.

[0050] like Figure 2 As shown, the surface morphology of the sample prepared by the method in Comparative Example 2 was observed by field emission scanning electron microscopy. The sample surface exhibits a "groove-like" appearance.

[0051] like Figure 6 As shown, the Raman characterization results of the sample prepared by the method in Comparative Example 2 are shown (WTO lines in the figure), which are identified as characteristic Raman peaks of titanium dioxide.

[0052] like Figure 15 As shown, the acoustic-thermal curve of the sample prepared by the method in Comparative Example 2 under ultrasonic conditions for 10 minutes (WTO line in the figure) shows that the titanium dioxide modified layer has good acoustic-thermal conversion ability.

[0053] like Figure 18As shown, the bacterial morphology (WTO) of the sample prepared by the method in Comparative Example 2, cultured with Staphylococcus aureus, is characterized with and without ultrasound. Without ultrasound, a large number of regularly shaped spherical bacteria are present on the sample surface. Under ultrasound, the number of bacteria on the sample surface is relatively reduced, and some bacterial surfaces are damaged. This confirms that the titanium dioxide modified layer prepared in Comparative Example 2 has a certain acoustic-thermal antibacterial ability under ultrasound response. Compared with the graphene / titanium oxide-based ternary heterojunction in Example 1, the graphene / titanium oxide-based ternary heterojunction has fewer bacteria on its surface, and the bacterial morphology is damaged. Combined with the bacterial morphology characterization results, the excellent acoustic-dynamic synergistic acoustic-thermal sterilization effect of the graphene / titanium oxide-based ternary heterojunction can be reflected.

[0054] Comparative Example 3 The preparation method of Comparative Example 3 differs from that of Example 1 in that methane was not introduced during the plasma-enhanced chemical vapor deposition process, i.e., no graphene film was constructed on the surface. Product A1 was obtained using micro-arc oxidation technology, and then A1 was placed in a plasma-enhanced chemical vapor deposition apparatus, with 80 sccm of argon gas and 5 sccm of hydrogen gas introduced, and treated at 750°C for 1 hour to obtain product A2, which is a titanium dioxide and titanium trioxide heterojunction (BTO).

[0055] like Figure 3 As shown, the surface morphology of the sample prepared by the method of Comparative Example 3 was observed by field emission scanning electron microscopy. It can be observed that the sample surface presents a "groove-like" appearance, which is not significantly different from the surface morphology of the sample prepared by Comparative Example 2.

[0056] like Figure 6 As shown, the Raman characterization results of the sample (BTO, line (b) in the figure) prepared by the method of Comparative Example 3 are identified as characteristic Raman peaks of titanium dioxide and titanium dioxide. This confirms that the sample prepared by the method of Comparative Example 3 is a composite material of titanium dioxide and titanium trioxide, i.e., a titanium oxide-based material.

[0057] like Figure 14 As shown, the ultrasonic response acoustic current test results of the sample (BTO, line (d) in the figure) prepared by the method of Comparative Example 3 are compared with those of pure titanium (Ti, line (a) in the figure) prepared in Comparative Example 1 and titanium dioxide (WTO, line (b) in the figure) prepared in Comparative Example 2. The titanium dioxide / titanium trioxide binary heterojunction (titanium oxide-based heterojunction, BTO) prepared in Comparative Example 3 has a significant ultrasonic response acoustic current. It can be seen that constructing a titanium oxide-based binary heterojunction is beneficial for responding to external field stimuli. In addition, by Figure 11 (d) BTO ultrasonic degradation of Rhodamine B and Figure 12(d) Results of BTO ultrasonic degradation of methylene blue: Compared to the graphene / titanium oxide-based ternary heterojunction, the ultrasonic catalytic degradation of rhodamine B and methylene blue by the titanium dioxide and titanium trioxide binary heterojunction prepared by the method in Comparative Example 3 was significantly weaker than that by the graphene / titanium oxide-based ternary heterojunction in Example 1. Based on the comparative results, it can be confirmed that constructing a graphene film on the surface of a titanium oxide-based heterojunction exhibits excellent ultrasonic catalytic performance.

[0058] Comparative Example 4 The preparation method of Comparative Example 4 differs from that of Example 1 in that: instead of using micro-arc oxidation technology to construct a titanium dioxide modified layer on the surface, a vertical graphene film is directly grown on the titanium surface using plasma chemical vapor deposition. A pure titanium sheet is placed in a plasma chemical vapor deposition apparatus, and the temperature is increased at a rate of 5°C / min to a reaction temperature of 750°C. The plasma generator power is set to 100W, and 80 sccm of argon, 5 sccm of hydrogen, and 2 sccm of methane are introduced. The reaction time is 1 hour, resulting in the formation of a vertical graphene film on the pure titanium surface.

[0059] like Figure 4 As shown, the surface morphology of the sample prepared by the method in Comparative Example 4 was observed by field emission scanning electron microscopy. It can be observed that the graphene on the sample surface exhibits a nanosheet structure, which increases the specific surface area of ​​the sample, and there are more edges of the nanosheets.

[0060] like Figure 7 As shown, this is the Raman spectroscopy result of the sample (VG, line (c) in the figure) prepared by the method of Comparative Example 4. The sample was measured at 1350 cm⁻¹. -1 1580cm -1 2700cm -1 The peaks at these locations are characteristic peaks, corresponding to the D peak, G peak, and 2D peak of graphene, indicating that graphene films can be constructed on titanium surfaces using this method.

[0061] like Figure 11 (e)VG lines and Figure 12 The VG line in (e) shows the ultrasonic catalytic degradation results of Rhodamine B and methylene blue in the sample prepared by the method in Comparative Example 4. The graphene film (VG) on the titanium surface showed virtually no effect on the catalytic degradation of Rhodamine B and methylene blue under ultrasonic conditions.

[0062] Comparative Example 5 The difference between the preparation method of Comparative Example 5 and Example 1 is that a two-step method is used to prepare the graphene / titanium oxide-based heterostructure. Specifically, based on the titanium dioxide modified layer, a titanium trioxide and titanium dioxide binary heterostructure is first formed, and then a vertical graphene film is formed on the surface. The preparation process is as follows: A titanium dioxide modified layer is prepared on the titanium surface using a micro-arc oxidation device. The electrolyte is a mixed solution of 38 g / L sodium tetraborate decahydrate and 14 g / L potassium hydroxide. A constant voltage mode of 400 V and a duty cycle of 20% are used, with an electrolytic oxidation time between 2 min and 15 min. This process prepares the titanium oxide modified layer on the titanium surface, yielding product Al. In other examples, the electrolyte can also be sodium silicate, sodium glycerophosphate, etc.; in other examples, anodic oxidation can also be used to prepare the titanium dioxide modified layer on the titanium surface. A1 was placed in a plasma chemical vapor deposition (PVD) apparatus with a plasma generator power of 100W, a heating rate of 5℃ / min, a reaction temperature of 750℃, and a reaction time of 1 hour. During the reaction, 80 sccm of argon and 5 sccm of hydrogen were introduced to form titanium trioxide (TiO2) in situ on the surface of the titanium dioxide-modified layer. Then, in the second step, a vertical graphene film was grown on the surface of A2 at a reaction temperature of 750℃ for 1 hour. During this reaction, 80 sccm of argon and 2 sccm of methane were introduced to obtain product A4. Through process adjustments, the first step forms a titanium dioxide-modified layer, the second step forms a titanium trioxide-titanium dioxide (TiO2-based) heterojunction, and the third step forms a vertical graphene film on the surface of the TiO2-based heterojunction. Samples prepared using this method are designated as BTO@VG-Two steps.

[0063] like Figure 5 As shown, the surface morphology of the sample prepared by the method in Comparative Example 5 was observed under a field emission scanning electron microscope. Nanosheet structures were grown on both the inner and outer pore surfaces of the porous structure, which confirms the existence of graphene nanosheets.

[0064] like Figure 12 As shown, the test results of the sample prepared by the method of Comparative Example 5 (BTO@VG-Two step, line (g) in the figure) in the ultrasonic response degradation of methylene blue are shown. The absorbance value of the methylene blue reagent peak of the control group without ultrasonic treatment (line (a) in the figure) is about 1.05, while the corresponding value of the sample prepared by Comparative Example 5 is about 0.72. This confirms that the sample has a certain catalytic degradation effect of methylene blue under ultrasonic stimulation. In addition, the corresponding value of the sample prepared by the method of Example 1 (BTO@VG, line (f) in the figure) is about 0.45. The ultrasonic degradation effect of methylene blue is much better than that of the sample prepared by Comparative Example 5, which confirms the superiority of the one-step in-situ construction of titanium dioxide and graphene films on the surface of titanium dioxide.

[0065] The above description is merely a partial embodiment and comparative example of a graphene / titanium oxide-based ternary heterostructure constructed using graphene as an example of a highly conductive thin film and titanium as an example of an implantable metal. It is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A responsive ternary heterojunction material, characterized in that, include: A titanium and its alloy metal substrate, an in-situ formed metal oxide modified layer on the surface of the metal substrate, and a variable valence metal oxide layer and a highly conductive thin film formed in one step on the surface of the metal oxide modified layer; wherein the metal oxide, the variable valence metal oxide and the highly conductive thin film form a ternary heterojunction; the variable valence metal oxide is miscible with the metal oxide and there is no obvious interlayer interface; the metal oxide modified layer is TiO2; the variable valence metal oxide is at least one of Ti2O3 and Ti3O5; and the highly conductive thin film is graphene nanosheets.

2. The responsive ternary heterojunction material according to claim 1, characterized in that, The thickness of the variable valence metal oxide layer is 10–5000 nm.

3. The responsive ternary heterojunction material according to claim 1, characterized in that, The thickness of the graphene nanosheets is <10 nm.

4. The responsive ternary heterojunction material according to any one of claims 1-3, characterized in that, The thickness of the metal oxide modified layer is <20 micrometers; the thickness of the highly conductive film is <500 nm.

5. A method for preparing a responsive ternary heterojunction material as described in any one of claims 1-4, characterized in that, include: (1) An oxidation technique is used to prepare a metal oxide modified layer on the surface of a metal substrate; (2) The metal substrate with the metal oxide modified layer on the surface is placed in a plasma-enhanced chemical vapor deposition device, and a precursor material is introduced to form a variable valence metal oxide layer and a highly conductive thin film in situ on the surface of the metal oxide modified layer.

6. The preparation method according to claim 5, characterized in that, The oxidation technology is anodic oxidation and / or micro-arc oxidation; The oxidizing electrolyte used in the anodic oxidation and micro-arc oxidation includes at least one of sulfuric acid, oxalic acid, hydrofluoric acid, sodium glycerophosphate, sodium hydroxide, potassium hydroxide, sodium tetraborate, and sodium silicate. The parameters for the anodic oxidation include: electrolyte concentration of 2–50 g / L, voltage range of 10–100 V, and time of 5–120 min. The parameters of the micro-arc oxidation include: electrolyte concentration of 5–100 g / L, voltage range of 280–700 V, time of 5–60 min, duty cycle of 5%–40%, and electrolyte temperature of 10–60 ℃.

7. The preparation method according to claim 5 or 6, characterized in that, The precursor material includes: a gaseous precursor or a liquid precursor; The gaseous precursor includes at least one of argon, hydrogen, methane, and acetylene; The liquid precursor includes at least one of titanium tetrachloride and titanium tetradimethylaminochloride.

8. The preparation method according to claim 7, characterized in that, When a gaseous precursor is selected, the parameters of the plasma-enhanced chemical vapor deposition equipment include: ionization power of the plasma generator of 50–400 W; background pressure of 0.1–1 Pa; pressure range of 20–1000 Pa; total flow rate of the gaseous precursor controlled at 20–500 sccm; reaction temperature of 400–800 ℃; and reaction time of 10–120 min.

9. The application of a responsive ternary heterojunction material according to any one of claims 1-4 in the preparation of a synergistic acoustic-thermal acoustic-dynamic bactericidal material, characterized in that, The responsive ternary heterojunction material responds to the external field and achieves acoustic-dynamic synergistic acoustic-thermal sterilization under ultrasonic conditions.

10. The application of a responsive ternary heterojunction material according to any one of claims 1-4 in the preparation of photothermal bactericidal materials, characterized in that, The responsive ternary heterojunction material responds to an external field and achieves photothermal sterilization under near-infrared light conditions.

Citation Information

Patent Citations

  • Modification method for titanium surface with osteogenic performance and antibacterial performance

    CN103014646B